Effect of mass fraction on tensile and bending strength of ramie/jute/e-glass composites - Nur Permata, Shafira; Firmansyah, Hendrix Noviyanto; Islam, Muhammad Irfa Nurul; Maulana, Indra (Teknik Mesin - Universitas Muhammadiyah Cileungsi, 2025)
Motorcyclist safety is highly influenced by the effectiveness of head protection, making material innovation in helmet manufacturing a primary focus particularly through the use of composite materials. This study aims to evaluate the mechanical properties of hybrid composites made from ramie, jute, and E-glass fibers, formulated with varying fiber mass fractions and epoxy resin as the matrix. The specimens were fabricated using the hand lay-up method and tested according to ASTM D638 for tensile strength and ASTM D790 for bending strength. The results showed that specimen D, which contained the highest mass fraction of E-glass fiber, demonstrated the best performance in tensile testing with an elastic modulus of 3062.244 MPa, tensile strength of 91.714 MPa, and the lowest strain at 2.14%, indicating high stiffness but brittle behavior. In contrast, specimen C, with the highest jute fiber content, had the lowest tensile modulus and strength, but the highest strain, indicating greater flexibility. In bending tests, specimen D showed the highest modulus of elasticity at 586.016 MPa, while specimen C recorded the highest flexural strength at 34.921 MPa. Macro observations revealed defects such as delamination, fiber breakage, and voids. The study concludes that fiber mass fraction significantly affects the mechanical properties of hybrid composites, and placing E-glass fibers in the outer laminate layers enhances flexural strength. This research contributes to the development of SNI-compliant helmets that are lightweight, strong, and environmentally friendly.